Periodicity in a delayed version of the kaldor trade cycle model - Frasson, M. V S; Gadotti, M. C. [UNESP]; Nicola, S. H J; Táboas, P. Z. (My University, 2013)
We are concerned with the Kaldor's trade cycle model under the effect of a delay which represents a gestation lag between a decision of investment and its effect on the capital stock. Taking the adjustment coefficient in the goods market as a bifurcation parameter, we achieve global branches of periodic solutions. In our setting the delay is a constant inherent to the specific economy. Copyright © 2013 Watam Press.
Keywords: Bifurcation; Delay equations; Global branch; Kaldor trade model; Periodic orbits